Efecto de la inclusión de ácidos grasos en la alimentación inicial de pollos de engorde sobre los parámetros productivos. - Piedra Quezada, Christel Paulette (Machala : Universidad Técnica de Machala, 2020)
This research work was carried out in the warehouse No. 1 of the Santa Inés farm of the Faculty of Agricultural Sciences (FCA) of the Technical University of Machala, Province of El Oro, whose objective was to evaluate the effect of the inclusion of fatty acids in the diet of Cobb 500 chickens on their productive parameters and the parameters to the canal, for them a Completely Random Design was used, where 200 Cobb 500 chickens were used, managed according to the poultry production standards established in the area For an open shed system, trying to apply the appropriate management to give a good temperature, adequate food and hydration, a basic vaccination schedule was used for the area that consisted of the use of Gumboro intermediate strain and Newcastle New Vac strain the Jack B1 JB. The balanced was prepared ecologically and with raw materials from the company ̋ BALMAR ̏, the birds were distributed in 5 groups: the Witness or Treatment 0 (Inclusion of palm oil in the balanced food), Treatment 1 (Inclusion of Soybean Oil in the balanced food), Treatment 2 (Inclusion of Sunflower Oil in the balanced food), Treatment 3 (Inclusion of Corn Oil in the balanced food) and Treatment 4 (Inclusion of yellow fat in the balanced food), each with four experimental units, in which 10 random chickens were placed. The variables to consider were, Live weight of the animal (g), Feed conversion index, Cumulative feed consumption (g), Cumulative water consumption (ml), Mortality, Weight before mortem (g), Bleeding weight (g) , Weight without feathers (g), Weight without viscera (g), Weight without head and without legs (g) and Thickness of abdominal fat (mm), at day 42 to perform the sacrifice, 2 animals per Unit were taken at random Experimental (male and female), obtaining the data of the 40-chicken carcass, a GRAM brand scale was used with a margin of error of ± 1g and the abdominal fat thickness data were obtained with a King's foot brand Kex Germany . For this, a completely randomized design was used, the statistical management of the data was used by the Statgraphics Centurion Program and a single-way ANOVA analysis was applied for all the variables and to observe possible differences and their confidence intervals the procedure was performed. multiple comparison of Bonferroni; with the exception of the mortality to which a Chi-Square Test was applied prior to the elaboration of the contingency tables. The results of the experiment show that the addition of balanced fatty acids present in palm, soy, sunflower and yellow fat oil used in the different treatments did not show any effect on live weight, conversion rate, water consumption, food consumption and mortality; nor does it show any effect on the data of ante mortem weights, bleeding, without feathers, without viscera and without legs - head of chickens, although if there was a significant difference in abdominal fat thickness, which may be due to the fatty acid composition present in the oils used in the experiments, the chickens that received the balanced oil containing palm oil presenting a greater abdominal fat deposit. In addition, the alternative of including yellow fat in balancing is interesting, due to its low cost and not directly interfering with the presence of excessive greasing in birds.
El presente trabajo de investigación se desarrolló en el galpón Nº 1 de la granja Santa Inés de la Facultad de Ciencias Agropecuarias (FCA) de la Universidad Técnica de Machala, Provincia de El Oro, cuyo objetivo fue evaluar el efecto de la inclusión de ácidos grasos en la dieta de pollos Cobb 500 sobre sus parámetros productivos y de los parámetros a la canal, para ellos se empleó un Diseño Completamente al Azar, donde se usaron 200 pollos Cobb 500, manejados de acuerdo a las normas de producción avícola establecidas en la zona para sistema de galpones abiertos, tratando de aplicar el manejo adecuado para dar una buena temperatura, alimentación e hidratación adecuada, se utilizo un calendario básico vacunal para la zona que consistía en la utilización de las vacunas de Gumboro cepa intermedia Y Newcastle New Vac cepa la sota. El balanceado fue elaborado ecológicamente y con materias primas provenientes de la empresa ̋ BALMAR ̏ , las aves fueron distribuidos en 5 grupos: el Testigo o Tratamiento 0 (Inclusión de aceite de palma en el alimento balanceado), Tratamiento 1 (Inclusión de Aceite de soja en el alimento balanceado), Tratamiento 2 (Inclusión de Aceite de girasol en el alimento balanceado), Tratamiento 3 (Inclusión de Aceite de maíz en el alimento balanceado) y Tratamiento 4 (Inclusión de grasa amarilla en el alimento balanceado), cada uno con cuatro Unidades experimentales, en las que se colocó 10 pollos al azar. Las variables a considerar fueron, Peso vivo del animal (g), Índice de conversión alimenticia , Consumo de alimento acumulado (g), Consumo de agua acumulada (ml), Mortalidad, Peso ante mortem (g), Peso al desangrado (g), Peso sin plumas(g), Peso sin vísceras(g), Peso sin cabeza y sin patas (g) y Espesor de grasa abdominal (mm), al día 42 para realizar el sacrificio, se tomaron al azar, 2 animales por Unidad experimental (macho y hembra), obteniendo los datos de la canal de 40 pollos, se empleó una balanza gramera marca CAMRY con un margen de error de ±1g y los datos de Espesor de grasa abdominal se obtuvieron con un Pie de Rey marca Kex Germany. Para ello se empleó un diseño completamente al azar, el manejo estadístico de los datos se usó el Programa Statgraphics Centurión y se aplicó análisis de una sola vía ANOVA para todas las variables y para observar posibles diferencias y sus intervalos de confianza se realizó el procedimiento de comparación múltiple de Bonferroni; con excepción de la mortalidad a la cual se le aplicó una Prueba de Chi-Cuadrado previo a la elaboración de las tablas de contingencia. Los resultados del experimento muestran que la adición en los balanceados de los acidos grasos presentes en el aceite de palma, soya, girasol y de grasa amarilla utilizados en los diferentes tratamientos no presentaron efecto alguno en peso vivo, índice de conversión, consumo de agua, consumo de alimento y mortalidad; tampoco evidencia un efecto alguno en los datos de pesos ante mortem, desangrado, sin plumas, sin vísceras y sin patas – cabeza de los pollos, aunque si se encontró diferencia significativa en espesor de grasa abdominal, que puede deberse a la composición de ácidos grasos presentes en los aceites usados en los experimentos, presentando un mayor depósito de grasa abdominal los pollos que recibieron el balanceado que contenía aceite de palma. Además, la alternativa de inclusión de la grasa amarilla en el balanceado se muestra interesante, por su bajo costo y al no interferir directamente con la presencia de un excesivo engrasamiento en las aves
Keywords: PESO; GRASA; MORTALIDAD; ACEITES